The Legal Status of Extrinsic Instruments for the Interpretation of Tax Treaties - Bossuyt, Jasper (IBFD Doctoral Ser., 2022)
National tax authorities can express their views in a variety of ways on how tax treaties should be interpreted. As a result, there are unilateral, bilateral and multilateral interpretive instruments that are not - or not necessarily - incorporated into an actual tax treaty, but are ""extrinsic"" to it. National courts and tax authorities, as well as taxpayers and tax scholars, strongly rely on the OECD Commentaries and Transfer Pricing Guidelines when interpr.